Estrategias didácticas interactivas para mejorar la enseñanza del idioma inglés, en los estudiantes de sexto grado de la escuela de egb Luis Humberto Benítez costa, período 2017 – 2018. - Armijos Armijos, Cristian Geovanny (2018)
The research Interactive didactic strategies to improve the teaching of the English language, in the sixth grade students of the school of EGB Luis Humberto Benítez Costa, period 2017 - 2018, whose objective was to apply interactive teaching strategies through pedagogical workshops to improve the teaching of the language English, in the sixth grade students of the School of EGB Luis Humberto Benítez Costa, period 2017-2018, was sustained in the descriptive study; methods: scientific, analytical, synthetic, inductive, deductive, hermeneutic and statistical; techniques: survey, interview, observation and knowledge test; instruments: observation sheet and questionnaire; and, the procedures: theoretical foundation, diagnosis, design, application and evaluation of the alternative. The use of a traditional teaching method and lack of motivation and student participation was diagnosed. 12 students and one teacher participated. Concluding that the interactive teaching strategies improves teaching and guarantees the development of communicative competence in students.